2009
DOI: 10.1590/s1020-49892009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de los servicios farmacéuticos de atención primaria del Sistema Único de Salud en Londrina, Paraná, Brasil

Abstract: These results can aid in restructuring the municipality's pharmaceutical services because they underscore the need to improve and to increase rational drug use as a therapeutic resource imperative to supporting health efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 5 publications
4
10
3
3
Order By: Relevance
“…31 The group of assistance indicators is composed of: average consultation time indicator; average dispensing time; percentage of drugs dispensed; percentage of properly labeled drugs; In relation to the average consultation time indicator, the six publications that presented results for this indicator. 6,[18][19]26,[32][33] showed that all the results found were below the time recommended by the World Health Organization, which establishes a minimum time for an adequate consultation, which must be at least 15 min long. However, the results presented by Brazil and Egypt were 8.6 min and 7.1 min, respectively, which demonstrates that despite not being within the specified limit, they are less critical than the other evaluated countries that presented values quite critical as in India, Kuwait, Pakistan and Bangladesh, where a variation was found between 1.96 min and 3.8 min for consultations.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…31 The group of assistance indicators is composed of: average consultation time indicator; average dispensing time; percentage of drugs dispensed; percentage of properly labeled drugs; In relation to the average consultation time indicator, the six publications that presented results for this indicator. 6,[18][19]26,[32][33] showed that all the results found were below the time recommended by the World Health Organization, which establishes a minimum time for an adequate consultation, which must be at least 15 min long. However, the results presented by Brazil and Egypt were 8.6 min and 7.1 min, respectively, which demonstrates that despite not being within the specified limit, they are less critical than the other evaluated countries that presented values quite critical as in India, Kuwait, Pakistan and Bangladesh, where a variation was found between 1.96 min and 3.8 min for consultations.…”
Section: Discussionmentioning
confidence: 82%
“…The average number of drugs prescribed per consultation was observed that all studies, which used this indicator, were above the value recommended by the World Health Organization (<2), however, three studies showed values close to this reference value. 7,[18][19][20] what the World Health Organization considers as reasonable up to two drugs per prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda que outros estudos tenham avaliado a disponibilidade de medicamentos em geral, e não somente aqueles destinados à Saúde Mental, os valores encontrados para este estudo estão acima da média nacional e de outras regiões 27,32,33 . A existência de alguns mecanismos para controle de estoques e participação do farmacêutico na etapa de programação na maioria das farmácias se opõe à falta de informação relacionada ao histórico de desabastecimento de cada um dos medicamentos, resultado já detectado em outro estudo realizado neste mesmo estado 32 .…”
Section: Discussionunclassified
“…De acuerdo con la OMS, el gasto en medicamentos en los países en desarrollo varía del 24% al 66%, y en países desarrollados de 7% a 30% del gasto total en salud. En el caso de los servicios farmacéuticos (SF) se recomienda el fortalecimiento de las políticas, de la gestión y de la atención a los pacientes [7]. La necesidad de evaluar la calidad de la atención en salud es de interés mundial, principalmente porque se entiende que una buena práctica terapéutica implica una buena atención a la salud [8].…”
Section: Introductionunclassified